Analisis Pengaruh Harga, Kepercayaan, dan Promosi Terhadap Keputusan Pembelian Pelanggan Aplikasi Shopee di Kota Bekasi - Hariyanto, Elsha Eka; Prasetyanta, Agus (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2024)
This study aims to examine the influence of price, trust, and promotion on the purchasing decisions of Shopee application customers in Bekasi City. The research method used is quantitative with a descriptive approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling method. The results indicate that the variables of price, trust, and promotion have a positive and significant effect on customer purchasing decisions. Multiple linear regression analysis and F-test indicate that these three variables simultaneously affect purchasing decisions. The Adjusted R2 value of 71.9% shows that a majority of the variability in purchasing decisions can be explained by price, trust, and promotion, while the remaining 28.1% is influenced by other variables not studied. Based on these findings, it is recommended that companies continue to offer competitive pricing, maintain customer trust by protecting personal data, and provide attractive promotions to enhance purchasing decisions.